Stability Investigation in the Optical Properties of Thermally Evaporated Ge5Se95-x Znx Thin Films - Mulama, Austine Amukayia; Mwabora, Julius Mwakondo; Oduor, Andrew Odhiambo; Muiva, Cosmas Mulwa; Muthoka, Boniface; Mbete, Drinold Aluda; Amukayia, Betty Namatsi (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Selenium-based chalcogenides are useful in telecommunication devices like infrared optics and threshold switching devices. The investigated system of Ge5Se95-xZnx (0.0 ‰¤ x ‰¤ 4 at.%) has been prepared from high purity constituent elements. Thin films from the bulk material were deposited by vacuum thermal evaporation. Optical absorbance measurements have been performed on the as-deposited thin films using transmission spectra. The allowed optical transition was found to be indirect and the corresponding band gap energy determined. The variation of optical band gap energy with the average coordination number has also been investigated based on the chemical bonding between the constituents and the rigidity behaviour of the systems network.